2018
DOI: 10.2217/pme-2018-0009
|View full text |Cite
|
Sign up to set email alerts
|

Preventive Effects of Oxytocin and Oxytocin Receptor in Breast Cancer Pathogenesis

Abstract: Aim: Modifications of oxytocin (OT) concentration and OT receptor (OXTR) expression level have different effects on breast cancer-derived cells. This study was conducted to evaluate OT variation in breast cancer patients and to evaluate OXTR expression changes in breast cancer tissues. Methods: The plasma concentrations of OT in both breast cancer patients and healthy individuals’ samples were assessed. OXTR variations were then assessed in both cancerous and noncancerous breast tissues. Results: OT had an inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 23 publications
1
17
0
Order By: Relevance
“…OT levels in the pituitary and blood also increased in a rat breast cancer model induced by N-methyl-nitrosourea (NMU)-treatment due to inhibition of insulin-regulated aminopeptidase (an oxytocinase) and decrease of catabolism of OT in the hypothalamus [57]. This is consistent with a human study, which observed higher OT plasma levels in breast cancer patients (n = 40) than in healthy individuals [58]. Higher OT plasma levels, however, do not mean higher OT levels in breast cancer tissue.…”
Section: Protective Effects Of Ot Against Breast Cancer Developmentsupporting
confidence: 84%
See 4 more Smart Citations
“…OT levels in the pituitary and blood also increased in a rat breast cancer model induced by N-methyl-nitrosourea (NMU)-treatment due to inhibition of insulin-regulated aminopeptidase (an oxytocinase) and decrease of catabolism of OT in the hypothalamus [57]. This is consistent with a human study, which observed higher OT plasma levels in breast cancer patients (n = 40) than in healthy individuals [58]. Higher OT plasma levels, however, do not mean higher OT levels in breast cancer tissue.…”
Section: Protective Effects Of Ot Against Breast Cancer Developmentsupporting
confidence: 84%
“…So far there exists only one study indicating that OTR expression in tumour tissues is lower (>11-fold at mRNA level and >2-fold at the protein level, n = 4) than in normal contralateral breast samples from the same individual. The authors of this study stated that a reduction of OTR expression in breast cancer could be effective in promoting cancer progression [58].…”
Section: Otr In Breast Cancermentioning
confidence: 91%
See 3 more Smart Citations